Investigation of the Microstructural Evolution during Hot Stamping of a Carburized Complex Phase Steel by Laser-Ultrasonics - Horn, Alexander; Merklein, Marion (Materials, 2021)
Prior carburization of semi-finished steel sheets is a new process variant in hot stamping to manufacture parts with tailored properties. Compared to conventional hot stamping processes, a complex phase typed steel alloy is used instead of 22MnB5. Yet recent investigations focused on final mechanical properties rather than microstructural mechanisms cause an increase in strength. Thus, the influence of additional carburization on the microstructural evolution during hot stamping of a complex phase steel CP-W(R)800 is investigated within this work. The phase transformation behavior, as well as the grain growth during austenitization, is evaluated by in-situ measurements employing a laser-ultrasound sensor. The results are correlated with additional hardness measurements in as-quenched condition and supplementary micrographs. The experiments reveal that the carburization process significantly improves the hardenability of the CP-W(R)800. However, even at quenching rates of 70 K/s no fully martensitic microstructure was achievable. Still, the resulting hardness of the carburized samples might exceed the fully martensitic hardness of 22MnB5 derived from literature. Furthermore, the carburization process has no adverse effect on the fine grain stability of the complex phase steel. This makes it more robust in terms of grain size than the conventional hot stamping steel 22MnB5.
CRIS-Team WoS Importer:2021-05-07
Keywords: hot stamping; phase transformation; quenching; grain growth; carburization